Double-Loop Learning in Islamic Boarding Schools: How Traditional Islamic Educational Institutions Reflect and Transform Organizations - Sofwan Manaf (Irfani, 2026)
This study investigates the implementation of double-loop learning within Islamic boarding schools (pesantren) in Indonesia, examining how these traditional educational institutions engage in organizational reflection and transformation while preserving their foundational Islamic values. Employing a qualitative multiple case study design, the research was conducted across three pesantren in Jakarta-Bogor   representing traditional (salafi), modern (khalafi), and integrated typologies through semi-structured interviews with 24 key informants including school leaders (kiai), senior teachers (ustadz), administrative managers, and alumni board members, supplemented by document analysis and non-participant observation over six months. Findings reveal that pesantren engage in double-loop learning through three interconnected mechanisms: (1) values-based reflective governance (muraja’ah tarbawiyyah), where institutional leaders systematically interrogate underlying assumptions of educational policies through consultative deliberation (musyawarah); (2) adaptive curriculum transformation, wherein pesantren reconcile classical Islamic scholarship (turath) with contemporary pedagogical demands without compromising doctrinal integrity; and (3) distributed leadership networks that enable bottom-up feedback loops from teachers and students to institutional decision-makers.